An ultrafast turn-on thiol probe for protein labeling and bioimaging. Issue 6 (17th February 2016) - Sun, Jinyu; Zhang, Liangwei; Zhang, Xiaolong; Hu, Yuesong; Ge, Chunpo; Fang, Jianguo
Abstract : A novel ultrafast turn-on thiol probe was developed that can be successfully applied to label protein thiols and imaging them in living cells. Abstract : A novel turn-on type of ultrafast biothiol fluorescent probe, Naph-EA-mal, was designed, synthesized and evaluated. The probe contains a naphthalimide moiety as a fluorophore, a maleimide unit as a thiol acceptor, and 1, 2-ethylenediamine as a linker.Naph-EA-mal displays high selectivity and a fast response toward thiols in aqueous solution. The reaction mechanism of the probe with thiols was confirmed by 1 H NMR and HRMS. Test strips were fabricated and a sharp color change was observed by the naked-eye. Furthermore, Naph-EA-mal was successfully applied to label protein thiols, image thiols in living cells, quantify thiol content in cells lysate, and determine the reversible protein thiols oxidation in fixed cells.